New MPPT method for stand-alone photovoltaic systems operating under partially shaded conditions - Bouilouta, A.; Mellit, Adel; Kalogirou, Soteris A. (My University, 2013)
A new method to track the global maximum power point (GMPP) under partially shaded conditions (PSCs), for stand-alone photovoltaic (PV) systems, is introduced. Two loads, static and dynamic, have been used to evaluate the effectiveness of the method under different PSCs. Simulation results show that the developed method guarantees convergence to the GMPP under different PSCs and provides fast convergence in rapid variation of insolation conditions. To assess the performance of the developed algorithm, a comparison between two algorithms recently published has been carried out. It is shown that the developed method outperforms other methods found in literature both in terms of efficiency (95.80% and 95% for static and dynamic load) and response time (less than 0.25s). Negligible oscillations around the MPP and easy implementation are the main advantages of the proposed method.
Keywords: Fuzzy logic; GMPP; MPPT; Photovoltaic systems; Predictive control; PSC